Investigate the equivalent weight effect on properties of perfluorosulfonic acid membrane in concentrated electrolytes. (1st November 2022) - Peng, Jing; Wei, Shuting; Goenaga, Gabriel; Weiss, Catherine M.; Neal, Christopher A.; Cantillo, Nelly; Zawodzinski, Thomas A.
Highlights: Equivalent weight effects on performance of PFSA membrane are investigated. Membrane with a lower EW exhibits higher water and acid uptake, and lower density. Conductivity and vanadium diffusivity are both controlled by EW of membranes. Donnan potential interprets partitioning effect and membrane-electrolyte interaction. Abstract: In this contribution, a series of characterizations, such as water uptake, acid uptake, membrane density, and conductivity measurements, have been utilized to study the effect of equivalent weights (EW) on ion partitioning and transport behavior of perfluorosulfonic acid membranes produced by 3M Corp. It is observed that water sorption and acid uptake both increase with a decrease in EW. This phenomenon results from a higher sulfonic acid site density in the membrane with a lower EW. Just as important, the Donnan potential opposing co-ion uptake on the membrane surface decreases with decreasing equivalent weight. The membrane with a lower EW is found to have a higher membrane density at the same water content, but the porosity does not show a large discrepancy among the three membranes we studied. Even though the higher acid concentration in membranes results in lower activity coefficients of ions, its higher water content still facilitates faster proton mobility and higher ion conductivity. This analysis helps draw a picture of the relationship between membrane morphology and dynamics of PFSA membranes. Graphical abstract: Image, graphical abstract